The Use of Color Words in Pamuk’s My Name is Red - Abdullah, Ayaz (Journal of Research in Humanities, 2023)
The paper analyzes the use of color words in Pamuk’s award winning novel, My Name is Red. The novel is rich in a variety of linguistic assets and represents newness in the use of color words with a Turkish backdrop. The study explores the frequency of color words and priorities them. To understand the symbolism associated with colors, the study looks for the linguistic contexts of color words. A total of eleven colors have been selected. One important feature of the study is analysis of the combination of natural and artificial color words.